A Directory of Diaghilev Dancers. (November 2019) - Foster, Andrew
Abstract : Serge Diaghilev's Ballets Russes came to an end with his death in 1929, but it has since been an endless source of fascination and inspiration for dancers, dance historians and fans. It would seem that every aspect of the Ballets Russes has been exhaustively explored and documented – from the art, the music and the choreography, to the personalities who created them. The names of Anna Pavlova, Tamara Karsavina and Vaslav Nijinsky are legendary, and many others (Michel Fokine, George Balanchine, Ninette De Valois, Marie Rambert) went on to influence and define the art of ballet for much of the 20th century. But what of the hundreds of dancers who actually gave life and form to the Ballets Russes? Who were they? Where did they come from? How long did they spend with the company? The following listing of more than 400 performers is a comprehensive record of the dancing artists who performed with Diaghilev's Ballets Russes.